2009
DOI: 10.1248/bpb.32.640
|View full text |Cite
|
Sign up to set email alerts
|

Docking Simulations and in Vitro Assay Unveil Potent Inhibitory Action of Papaverine against Protein Tyrosine Phosphatase 1B

Abstract: Natural products have played an important role in treating and preventing human diseases.1) An analysis of the origin of the drugs that were launched in the last twenty-five years showed that both natural products and semi-synthetic compounds, derived from natural origin, comprised 34% of all new chemical entities, while 18% of them were synthetic mimics of natural compounds.2) Therefore, natural products are considered important sources for new drugs or lead optimization.2,3) The structural diversity of natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…(168)(169)(170) inhibited PTP 1B in the mixed-type manner, indicating that they may bind both at the active site and an additional binding site of the PTP 1B enzyme. 179 The genus Siegesbeckia has been used as a traditional medicine, ''Hi-Chum'' in Korea (common name: Siegesbeckia herb), to treat inflammatory diseases.…”
Section: O Isoxazole Carboxylic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…(168)(169)(170) inhibited PTP 1B in the mixed-type manner, indicating that they may bind both at the active site and an additional binding site of the PTP 1B enzyme. 179 The genus Siegesbeckia has been used as a traditional medicine, ''Hi-Chum'' in Korea (common name: Siegesbeckia herb), to treat inflammatory diseases.…”
Section: O Isoxazole Carboxylic Acidsmentioning
confidence: 99%
“…Papaverine also exhibited potent in vitro inhibitory effect against recombinant h-PTP 1B (IC 50 1.20 mM) and significantly decreased fasting blood glucose level in vivo. 170 The genus Erythrina of the family Leguminosae comprises over 110 species that are widely distributed in tropical and subtropical regions, and representative species have been used in indigenous medicine. 171,172 In a continuing effort to search for natural PTP 1B inhibitors, Na et al reported three new 2-arylbenzofurans isolated from the stem bark of Erythrina addisoniae, which were found to exhibit potent in vitro PTP 1B inhibitory activities.…”
Section: O Isoxazole Carboxylic Acidsmentioning
confidence: 99%
“…76 Chen et al demonstrated that berberine has insulinmimicking effects on both adipocytes and myocytes, which may occur through the inhibition of PTP1B activity and signicantly lower the blood glucose of diet-induced-obese (DIO) mice and db/db mice, but they do not increase insulin release and synthesis in vivo. 78 Three norditerpenoid alkaloids, nigelladines AÀC, and one pyrroloquinoline alkaloid, nigellaquinomine, possessing new skeletons were isolated from the seeds of Nigella glandulifera Freyn. 77 Papaverine (101, Fig.…”
Section: Alkaloidsmentioning
confidence: 99%
“…Inspired by the structural similarity with 283, papaverine 284 was inferred to exhibit inhibitory activity. It was shown that 284 readily docked within the binding pocket of PTP1B in a low-energy orientation via an optimal set of attractive interactions [189] . Compound 284 exhibited a potent in vitro inhibitory effect (IC 50 =1.20 μmol/L), and significantly decreased fasting blood glucose levels of Balb/c mice in vivo.…”
Section: N-or S-containing Compoundsmentioning
confidence: 99%